RISK FACTORS OF BIRTH ASPHYXIA - Majeed, Rehana; Memon, Yasmeen; Majeed, Farrukh; Shaikh, Naheed Parveen; Rajar, Uzma DM (Journal of Ayub Medical College Abbottabad, 2007)
Background: Birth asphyxia is a serious clinical problem worldwide. There are many reasons a baby may not be able to take in enough oxygen before, during, or just after birth. Damage to brain tissues is a serious complication of low oxygen that can cause seizures and other neurological problems. This study was designed to asses the risk factors of birth asphyxia in neonates. Methods: This descriptive, prospective study was conducted in the Department of Paediatrics, Isra University Hospital, Hyderabad, from April 2005 to April 2006. 125 newborn (75 males and 50 females) admitted to the neonatal care unit, who were delivered with delayed cry or low apgar score (<7) were included. Detailed maternal history was taken, regarding their age, gestational age, and complications, if any. Results: Out of 125 neonatal encephalopathy cases, 28% were diagnosed as suffering with moderate or severe encephalopathy, whereas 36% had mild encephalopathy. Risk of neonatal encephalopathy increased with increasing or decreasing maternal age. Antepartum risk factors included non-attendance for antenatal care (64%). Multiple births increased risk in 4.8%. Intrapartum risk factors included non-cephalic presentation (20%), prolonged rupture of membranes (24%) and various other complications. Particulate meconium was associated with encephalopathy in 9.6%. 60% mothers were anemic. Vaginal bleeding was strongly associated with birth asphyxia in 34.44% of neonates. 56% of mothers delivered at home, while 28% delivered at a private hospital or maternity home. Only 12% delivered at a tertiary care hospital. Conclusion: Lack of antenatal care, poor nutritional status, antepartum hemorrhage and maternal toxaemia were associated with higher incidence of asphyxia. Improvements in the public health of women with associated gains in female growth and nutrition must remain a longer-term goal. Early identification of high-risk cases with improved antenatal and perinatal care can decrease such high mortality. Safe motherhood policy is recommended. Key words: Risk factor; Birth asphyxia; Hypoxic ischemic encephalopathy (HIE)